The impact of hybrid learning in teaching English for Business Communication in Vocational Higher Education of Indonesia - Andi Musdariah; Muhammad Basri; Baso Jabu (Center for Humanities and Innovation Studies, 2021)
Some studies have been undertaken to decide the impact of hybrid learning on outcomes in higher education settings, with findings indicating that hybrid learning increases student performance more than distant learning or normal face-to-face instruction. This paper focuses on the students’ perspective on the impact of hybrid learning-based instruction in teaching English for Business Communication in Vocational Higher Education of Indonesia. This study is ex post facto research that aims to find the causes that allow changes in behavior, symptoms, or phenomena caused by an event, behavior, or things that cause changes in the independent variables which have occurred. This study employed a case study using students’ reflection journals and online questionnaires to seventy-five students of Business English for Communication class of the Vocational Higher Education in Makassar, South Sulawesi, Indonesia. Data were analyzed descriptively. In analyzing the data, the researcher used thematic analysis and content analysis. Data analysis steps are data familiarization, generating initial codes, searching for themes, reviewing themes, defining and naming themes, and producing the report. This study showed that students perceived the hybrid learning improved students’ technology competence, collaboration participation, and engagement, motivation, self-confidence. The impact of hybrid learning in teaching English for Business Communication can be categorized into three highly impacted, moderately impacted, and lowly impacted on students, attitude, skills and competence, and motivation. This study claims that the more positive students are toward hybrid learning education in the classroom, the higher their English for Business Communication performance. This research improves scholarly understanding of hybrid learning instruction in Indonesian Vocational Higher Education when teaching English for Business Communication.